Subgingival microbiota from Cebus apella (capuchin monkey) with different periodontal conditions - Jardim Júnior, Elerson Gaetti [UNESP]; Monti, Lira Marcela [UNESP]; Nicolas Ciesielski, Francisco Isaak [UNESP]; Gaetti-Jardim, Ellen Cristina [UNESP]; Okamoto, Ana Cláudia [UNESP]; Schweitzer, Christiane Marie [UNESP]; Avila-Campos, Mario Julio (Elsevier B.V., 2012)
This present study evaluated the subgingival microbiota of the Cebus apella with different periodontal conditions kept by the Tufted Capuchin Monkey Procreation Center (São PauloState University - UNESP) or free-ranging monkeys. For this purpose, clinical specimens of subgingival biofilm were collected from 52 monkeys, of both genders, 40 kept in captivity and 12 free-ranging monkeys. The primates were submitted to periodontal evaluation and biofilm samples were transferred to VMGA III transport medium and ultrapure water. The microbiota was cultivated in selective and non-selective culture media and microbial DNA was extracted and the presence of periodontal pathogens was evaluated using PCR and real-time PCR. The actinomycetes, fusobacteria, Campylobacter rectus, Eikenella corrodens, black-pigmented Gram-negative anaerobic rods, Tannerella forsythia, staphylococci and streptococci represent the predominantly detected microorganisms. Aggregatibacter actinomycetemcomitans, Dialister pneumosintes and Prevotella nigrescens were rarely observed, whereas Treponema denticola was not found. Populations of C. rectus, E. corrodens, Fusobacterium nucleatum, Porphyromonas gingivalis, Prevotella intermedia, T forsythia and the total microbial load were significantly higher in animals with bone loss and, in smaller extension, in animals with gingival bleeding. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Periodontitis; Non-human primates; Anaerobes; Infection